2017
DOI: 10.4103/1735-9066.205953
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability of the persian practice environment scale of nursing work index

Abstract: Background:The practice environment pivotal role in patients and nurses better outcomes is evident. Practice Environment Scale of Nursing Work Index (PES-NWI) is widely utilized to assess nursing work environments. The present study was conducted to demonstrate the validity and reliability of the Persian version of PES-NWI.Materials and Methods:The instrument was translated and its psychometrics were investigated by content, construct validity (factor analysis), and homogeneity (internal consistency and intrac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
8
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
4
8
0
1
Order By: Relevance
“…These findings are congruent with those from other studies where using CFA, investigators demonstrated adequate to good model fit using the same or similar PES-NWI factor structure (Elmi et al, 2017;Havens et al, 2012). Elmi et al (2017) reported CFI and nonnormative fit indices (also known as TLI) as >0.90, which is consistent with our findings. A difference between our analysis and Elmi et al′s (2017) is that our χ 2 and RMSEA values were inflated due to the large sample size.…”
Section: Confirmatory Factor Analysis Modelssupporting
confidence: 93%
See 2 more Smart Citations
“…These findings are congruent with those from other studies where using CFA, investigators demonstrated adequate to good model fit using the same or similar PES-NWI factor structure (Elmi et al, 2017;Havens et al, 2012). Elmi et al (2017) reported CFI and nonnormative fit indices (also known as TLI) as >0.90, which is consistent with our findings. A difference between our analysis and Elmi et al′s (2017) is that our χ 2 and RMSEA values were inflated due to the large sample size.…”
Section: Confirmatory Factor Analysis Modelssupporting
confidence: 93%
“…Elmi et al (2017) reported CFI and nonnormative fit indices (also known as TLI) as >0.90, which is consistent with our findings. A difference between our analysis and Elmi et al′s (2017) is that our χ 2 and RMSEA values were inflated due to the large sample size.…”
Section: Confirmatory Factor Analysis Modelssupporting
confidence: 92%
See 1 more Smart Citation
“…Obstajajo različni instrumenti za merjenje psihološkega stresa ter obremenitev na delovnem mestu (Nuebling, et al, 2006), oceno delovnega mesta zaposlenega (Bai, et al, 2015), vpliva delovnega okolja na klinično prakso v zdravstveni negi (Elmi, et al, 2017;Jing, et al, 2017;Ogata, et al, 2018) in oceno zdravega delovnega okolja (Huddleston, et al, 2017).…”
Section: Uvodunclassified
“…Referring to the tools used to measure the work climate in health services, we find several different instruments (Elmi et al, 2017 ), some of which are specific to concrete professions, such as nursing (Olsen et al, 2017 ) or anesthesiology (Rama-Maceiras et al, 2012 ), and certain fields such as mental health (Ehrhart et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%